Neuropsychological Formulation A Clinical Casebook - Macniven, Jamie A.B (Springer International Publishing : Imprint: Springer, 2016)
Jamie A. B. Macniven Clin.Psy.D., editor This forward-looking reference defines and illustrates the process and themes of formulation in neuropsychology and places it in the vanguard of current practice. The book explains the types of information that go into formulations, how they are gathered, and how they are synthesized into a clinically useful presentation describing psychological conditions resulting from neurological illness or injury. Cases highlight the relevance and flexibility of narrative- and diagram-based formulation methods in approaching a diverse range of issues and conditions, from decisional capacity to cultural considerations, Huntington's disease to deep dyslexia. Throughout this volume, formulation is shown as integral to treatment and rehabilitation planning alongside clinical assessment, cognitive testing, and diagnosis. Included among the topics: The interface of neuroimaging with neuropsychological findings in traumatic brain injury. Neuropsychological aspects of temporal-lobe epilepsy: seeking evidence-based practice. An integrative approach to differential diagnosis of subarachnoid hemorrhage and Korsakoff's dementia. Educational disengagement following mild TBI in childhood. Themes in the formulation of repeat assessments. Cognitive neuropsychological formulation. Formulation is essential in good neuropsychological assessment as it provides the foundation for appropriate intervention by bringing together the results of different evaluations into a coherent whole. . . . Macniven's compelling and constructive book has assembled internationally known experts from diverse backgrounds to provide illumination of their own views and approaches to formulation, which makes the book a pleasure to read and should establish it as essential reading on clinical psychology and neuropsychology training courses. - Professor Barbara A. Wilson OBE, Ph.D., D.Sc. Neuropsychologists, clinical psychologists, and rehabilitation specialists will find Neuropsychological Formulation of critical importance not only to the literature of the field, but also to the developing role of clinical neuropsychology within healthcare systems. .